EFEKTIFITAS MANAJEMEN KEPEMIMPINAN DALAM MENCIPTAKAN GOOD GOVERNANCE - Enong Rostiawati (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
This study aims to find out about the effectiveness of leadership management and its influence, in order to create good governance, in the work environment of regency/city governments in Banten Province. Leadership has a very strategic and important role in creating a government that supports good governance. Therefore, education and training for leaders are needed to strengthen their leadership management in each institution. This study uses a quantitative survey type approach. This study uses a quantitative approach with survey. Data collection techniques carried out through; observation, interview, documentation, and questionnaire. The questionnaire was tested to test the validity, reliability and objectivity of the instrument, with the total item correlation technique which is the basis of the Pearson correlation. The results obtained were seven interval classes with the highest significance acquisition at grade interval 4 (32.50%) and the lowest at grade interval 7 (2.50%). The survey instrument includes 4 aspects of implementation, 1) mentoring, 2) reviewing, 3) evaluation, and 4) monitoring. The results showed that it is very important to conduct training in order to improve management quality. The government has assessment guidelines for leaders who will take leadership training